Unintentional ingestion of putative delta-8 tetrahydrocannabinol by two youth requiring critical care: a case report - Erin K. Bradley; Brooke E. Hoots; Evan S. Bradley; Douglas R. Roehler (BMC, 2023)
Abstract Background Delta-8 tetrahydrocannabinol (THC) is a psychoactive cannabinoid from the cannabis plant that can be synthetically converted from cannabidiol (CBD). Most states permit the full or restricted sale of hemp and hemp-derived CBD products, and therefore, delta-8 THC products are on the rise. Delta-8 THC consumption can cause intoxication. Products are often sold in edible form and occasionally in packaging that appears similar to candy. Clinical presentations for delta-8 THC ingestions are understudied and may differ from those described for delta-9 THC ingestions. Case presentation This case report describes unintentional ingestions of putative delta-8 THC by two pediatric patients that results in admission to the pediatric intensive care unit. The ingestions were of putative delta-8 THC infused product that resembled popular candies. Both patients developed periods of bradypnea with continued intermittent periods of agitation. Medical intervention included observation, noninvasive positive pressure ventilation via high flow nasal cannula, and intubation-but was not needed for both patients. Although family noted ongoing irritability for the patients, both were discharged approximately 45 h after ingestion. Delta-8 THC ingestion is reliant on self-report. Conclusions As the availability of delta-8 THC increases, along with associated pediatric exposures, it is imperative for health care providers to quickly recognize and provide adequate treatment. While there is no specific antidote for THC intoxication beyond supportive care, providers can play an important role in prevention by educating parents and guardians on safe cannabis storage and by documenting cases for adverse event monitoring.